2004
DOI: 10.1007/s10753-004-6047-y
|View full text |Cite
|
Sign up to set email alerts
|

RSV Causes HIF-1α Stabilization via NO Release in Primary Bronchial Epithelial Cells

Abstract: RSV infection is characterized by airway edema. Stabilization of hypoxia inducible factor-1alpha (HIF-1alpha) is important in both inflammation and edema formation. In this study we evaluated whether RSV induced release of nitric oxide (NO) by bronchial airway epithelial cells leading to the stabilization of HIF-1alpha and subsequent transcription of VEGF(165). Primary human bronchial epithelial cells (HBEpC) were used; cell supernatants were analyzed. Western blot analysis was used for the detection of HIF-1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…Although recent studies suggest the involvement of HIF-1 in airway epithelial responses to viral infection (38) and in inflammatory signaling or subepithelial remodeling during allergic airway inflammation (32), chronic obstructive pulmonary disease (33), or idiopathic pulmonary fibrosis (68), the importance of HIF-1␣ activation and the involvement of NO in these conditions is not clear at present. Analogous to previous studies showing biphasic regulation of cell migration by TNF-␣, with initial activation of filopodia and increased cell migration followed by inhibition of cell migration and up-regulation of p53 at later stages (54), our results may suggest that the induction of NO production during inflammation may similarly be involved in such biphasic regulation of epithelial cell migration to assure coordinated wound repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies suggest the involvement of HIF-1 in airway epithelial responses to viral infection (38) and in inflammatory signaling or subepithelial remodeling during allergic airway inflammation (32), chronic obstructive pulmonary disease (33), or idiopathic pulmonary fibrosis (68), the importance of HIF-1␣ activation and the involvement of NO in these conditions is not clear at present. Analogous to previous studies showing biphasic regulation of cell migration by TNF-␣, with initial activation of filopodia and increased cell migration followed by inhibition of cell migration and up-regulation of p53 at later stages (54), our results may suggest that the induction of NO production during inflammation may similarly be involved in such biphasic regulation of epithelial cell migration to assure coordinated wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 not only mediates adaptive responses to hypoxia but is also recognized to play important roles in inflammatory processes (31), and recent studies have demonstrated HIF-1␣ activation during chronic airway inflammation (32,33), conditions typically associated with increased NOS2 expression. Although it is well appreciated that HIF-1 can be activated under normoxic conditions by inflammatory cytokines (34 -36) or bacterial or viral stimuli (37,38), which was in some cases attributed to intermediate NO production (38), the significance of HIF-1 in mediating airway inflammation and/or injury is only beginning to be appreciated.…”
mentioning
confidence: 99%
“…Viral infection is generally appreciated to induce stabilization of HIF-1α in target cells, which consequently contributes to local inflammation. For example, the common upper respiratory tract pathogen respiratory syncytial virus (RSV) induces HIF-1α in primary human bronchial epithelial cells via a NO-dependent pathway [29]. Increased HIF-1α levels stimulates VEGF production, enhancing monolayer permeability, which may play a role in the airway edema of acute RSV infection.…”
Section: Hif-1α Dynamics In Viral Infectionmentioning
confidence: 99%
“…VSV can induce HIF-1α stabilisation in bronchial cells, potentially contributing to the clinical airway oedema of acute VSV infection (Kilani et al, 2004). Other viruses also induce HIF-1α stabilisation (see 1.2.3.3.2).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear antigens of Epstein-Barr virus bind to PHD, inhibiting HIF-1α degredation (Darekar et al, 2012). The respiratory tract pathogen respiratory syncytial virus (RSV) induces HIF-1α in human bronchial cells via a NO-dependent pathway, and the resultant increased VEGF also enhances monolayer permeability, a pathway which may contribute to airway oedema of acute RSV infection (Kilani et al, 2004). Hypoxia-independent stabilization of HIF-1α in vitro and in vivo has also been observed in another study of RSV (Haeberle et al, 2008), further supporting HIF-1α stabilisation occurring as a result of a viral infection.…”
Section: Hif-1α and The Immune Response To Viral Pathogensmentioning
confidence: 99%